2018
DOI: 10.1111/famp.12412
|View full text |Cite
|
Sign up to set email alerts
|

EMBRace: Developing a Racial Socialization Intervention to Reduce Racial Stress and Enhance Racial Coping among Black Parents and Adolescents

Abstract: Researchers have illustrated the deleterious psychological effects that racial discrimination has exerted on Black Americans. The resulting racial stress and trauma (RST) from experiences with discrimination has been linked to negative wellness outcomes and trajectories for Black youth and families. Racial socialization (RS)—defined as the verbal and nonverbal messages that families use to communicate race to their children—can be a cultural strength and has been associated with positive outcomes in Black yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 69 publications
1
106
0
Order By: Relevance
“…Community members and former study participants also provided input regarding session content and flow and general recruitment strategies through focus groups. Additional information regarding the intervention can be found in a feasibility and acceptability study [ 17 ] and a forthcoming development paper [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Community members and former study participants also provided input regarding session content and flow and general recruitment strategies through focus groups. Additional information regarding the intervention can be found in a feasibility and acceptability study [ 17 ] and a forthcoming development paper [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…This pandemic has shown that communities of color suffer disproportionately from the disease in the United States, which is not surprising given the additive, adverse effects of racism and other harmful sociopolitical conditions (Anderson, McKenny, & Stevenson, 2019; Waite et al, 2020; Watson, 2019a,b). For example, social risk factors (i.e., racism) contribute to African American mothers having significantly higher rates of premature births and infant and maternal deaths regardless of class and educational status (Anderson et al, 2019).…”
Section: Cultural Values and The Healthcare Systemmentioning
confidence: 99%
“…), game system (i.e., environment, mechanics, visual design, animations, etc. ), and computational model embedded within Passage Home [7] were developed through a multi-year interdisciplinary designbased research effort conducted in collaboration with clinicians and researchers from an RES clinical intervention called the Engaging, Managing, and Bonding through Race (EMBRace) program [8]. The Racial Encounter Coping Appraisal and Socialization Theory (RECAST) [3] provides a model for understanding the effects of racial socialization on racial coping and self-efficacy for addressing racialized stress.…”
Section: Methods 21 Passage Homementioning
confidence: 99%